Validation of the Portuguese Version of Community Attitudes towards People with Mental Illness (CAMI) - Lopes, Inês Cardoso Pinto (2021)
Stigma remains a feature that influences the lifestyle of people with mental illness. Negative attitudes , sterotypes and discrimination are still prevalent in these people`s life. Stigma is considered a public health problem that occurs unconsciously in society, categorizing people. Portugal is the seventh worst country in relation to stigma in Mental Health. There have been few improvements in the reduction of stigma over time and there is a great need to create investigations and validate instruments that measure stigma in the population. This study aims to contribute to adress the gaps in the levelof studies and normative instruments that measure the stigma of the Portuguese population in the face of mental illness. It therefore aims to adapt and validate CAMI culturally and examine its psychometric properties. The 27 item version of CAMI was translated and retroversion, wich was analyzed and evaluated by a panel of experts. A socio-demographic survey and the CAMI participated online, in wich 427 adults representing the Portuguese population in general participated. Finally, the reliability and validity of the instrument were analyzed. There are levels of stigma in the Portuguese populationthat vary according to sociodemographic characterisitics such as gender, age and vontact with mentally ill people. CAMI has positive values of reliability and validity. This study contributed to the achievement and validation of new measures to assess the stigma of the general population related to people with Mental Illness. We must continue to analyze this theme and understand over time the existing levels of stigma, its predominance in society and the possible creation and implementation of new measures that support mental disease literacy and anti-stigma.